Effect of thin capitalization, intellectual capital and independent commisioners on effective tax rate - Upita Sari; Sekar Mayangsari (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2025)
Purpose – This research aims to determine the influence of thin capitalization, intellectual capital, and independent commissioners on effective tax rates, while also addressing a growing issue in the industrial sector. Methods – A quantitative approach was utilized, employing an explanatory research strategy and purposive sampling technique. The sample population consisted of 41 companies, with data sourced from their annual financial reports. The data analysis included multiple linear regression, classical assumption testing, hypothesis testing using t-tests, and the coefficient of determination; SPSS statistical tools facilitated this analysis. Findings – The study found that thin capitalization, intellectual capital, and the role of independent commissioners significantly influence company performance and corporate tax avoidance, highlighting the importance of this research in the manufacturing sector. Implications - These findings have practical implications for company management. They suggest that intellectual capital can be an effective tool for managing effective tax rates, while the role of independent commissioners warrants careful evaluation. Conversely, thin capitalization appears to have minimal impact on effective tax rates. Originality – This research underscores the need to assess the effectiveness of independent commissioners in ensuring tax efficiency for consumer goods companies, as well as the necessity of protecting intellectual capital. This highlights the originality and significance of the study in the manufacturing field.